2020
DOI: 10.3390/ijerph17165705
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Aggression as Explanatory Variables of Cyberbullying in Spanish Preadolescents

Abstract: There is a growing interest in preventing cyberbullying in youth. However, multiple questions remain as to the relationship between cyberbullying and psychosocial variables. This study examines the relationship between personality traits, aggression and cyberbullying (victims, bullies, victimized bullies and not involved) in 548 Spanish students aged 10 to 13 (50.2% boys). To do so, the Screening of Peer Harassment, the Big Five Questionnaire for Children and the Aggression Questionnaire were used. Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
3
18
1
2
Order By: Relevance
“…Cavalcanti and Pimentel (2016) further found direct effects of neuroticism extraversion and Agreeableness in physical aggression, which was not found in this study. Further, Escortel et al (2020) indicated that the extraversion trait had been an explanatory factor in cyber bullying victims.…”
Section: Discussionmentioning
confidence: 99%
“…Cavalcanti and Pimentel (2016) further found direct effects of neuroticism extraversion and Agreeableness in physical aggression, which was not found in this study. Further, Escortel et al (2020) indicated that the extraversion trait had been an explanatory factor in cyber bullying victims.…”
Section: Discussionmentioning
confidence: 99%
“…Second, several studies explored how students were immersed in different CB situations from different roles (Schultze-Krumbholz, Hess, Pfetsch, & Scheithauer, 2018). Most of them evaluated the bully, victim and witness roles (5 articles), but others only investigated victims (4 articles), witness (3 articles) or bully and victims (Chu, Fan, Liu, & Zhou, 2018b;Escortell, Aparisi, Martínez-Monteagudo, & Delgado, 2020).…”
Section: Purpose/smentioning
confidence: 99%
“…Among the recent studies examining cyberbullying prevalence among primary school students, Aizenkot [ 28 ] reported that 7.8% of the Israeli participants were cyber-victimized in their Whatsapp group chat. Escortell et al [ 29 ], assessing 15 electronic harassment behaviours in a sample of 548 Spanish students aged 10 to 13 from Alicante, found that 18% of the participants reported suffering cybervictimization. In a series of studies with students in years 3 to 6 of primary school in Catalonia (Spain), Sidera et al found that 14.4% of the participants have suffered at least one online aggression in the last month [ 30 ] and 4.4% were cyber victims with a minimum frequency of once or twice a month [ 31 ].…”
Section: Introductionmentioning
confidence: 99%